High-Dose Cytarabine and Autologous Stem-Cell Transplantation in Mantle Cell Lymphoma: Long-Term Follow-Up of the Randomized Mantle Cell Lymphoma Younger Trial of the European Mantle Cell Lymphoma Network. Issue 3 (5th December 2022) - Hermine, Olivier; Jiang, Linmiao; Walewski, Jan; Bosly, André; Thieblemont, Catherine; Szymczyk, Michal; Pott, Christiane; Salles, Gilles; Feugier, Pierre; Hübel, Kai; Haioun, Corinne; Casasnovas, René Olivier; et al.
Abstract : Clinical trials frequently include multiple end points that mature at different times. The initial report, typically based on the primary end point, may be published when key planned co-primary or secondary analyses are not yet available. Clinical Trial Updates provide an opportunity to disseminate additional results from studies, published in JCO or elsewhere, for which the primary end point has already been reported. In 2004, the European Mantle Cell Lymphoma (MCL) Network initiated the randomized open-label, phase III MCL Younger trial for first-line treatment of patients with advanced-stage MCL, age < 66 years, comparing an alternating rituximab plus cyclophosphamide, doxorubicin, vincristine, and prednisone/rituximab plus dexamethasone, high-dose cytarabine, and cisplatin (R-CHOP/R-DHAP) induction followed by high-dose cytarabine-containing myeloablative radiochemotherapy conditioning and autologous peripheral blood stem-cell transplantation (R-DHAP arm) to R-CHOP with standard myeloablative radiochemotherapy and autologous stem-cell transplantation (R-CHOP arm). After a median follow-up of 10.6 years, the time to treatment failure was still significantly improved in the R-DHAP versus R-CHOP arms (medians 8.4 v 3.9 years, 5-/10-year rates 64%/46% v 41%/25%, P = .038, hazard ratio, 0.59). Median overall survival (OS) was not reached in the R-DHAP arm versus 11.3 years in R-CHOP arm (5-/10-year rates, 76%/60% v 69%/55%, P = .12). The unadjusted OS hazard ratios (0.80 [95% CI, 0.61 to 1.06], P = .12) reached significance when adjusted for Mantle Cell Lymphoma International Prognostic Index (MIPI) and MIPI + Ki-67 (MIPI-c) (0.74; 95% CI, 0.56 to 0.98; P = .038 and .60; 95% CI, 0.41 to 0.87; P = .0066). The incidence of secondary hematologic malignancies tended to be higher in the R-DHAP arm (4.5% v 1.4% at 10 years). With mature long-term data, we confirm the previously observed substantially prolonged time to treatment failure and, for the first time to our knowledge, show an improvement of OS. Some patients with MCL may be cured.